Alokasi Dana Desa dalam Formulasi Kebijakan APBD Kabupaten Jember Tahun 2012 - Fastari, Agisma Dyah Fastari Dyah Fastari; Wasiati, Inti; B, Boedijono (e-Sospol)
AbstractVillage Fund Allocation is one type of direct financial assistance for villages given by the regency government taken 10% of balance funding of DAU (General Allocation Fund) and DAK (Special Fund Allocation) of the central board. Village Fund Allocation, often referred to as ADD, has its own rules in its establishment. The rules are stated in the legislation; that is, in PERMENDAGRI (Ministry of Internal Affairs Regulation) No. 37 Year 2007 which is set out in Jember Local Regulation No. 3 Year 2007. Jember Regency government establishes ADD because of lack of village income to finance its own operation. ADD becomes very important since, without ADD or other direct financial assistance to village, it will not exist. ADD which is a form of budget, in its stipulation is included in the budget formulation process. This research was conducted to identify the allocation process of ADD in the local budget policy formulation of Jember Regency in 2012 by applying descriptive-qualitative research method. The research results of were that Jember Regency government in the allocation of ADD, a little bit disregarded the fairness principle and overstated the equity principle. In PERMENDAGRI it is stated that equity principle is in line with the regional conditions. However, in reality, the local government of Jember Regency allocated ADD without considering this. Among villages is only a little difference in allocation. In fact, if using the fairness principle, It would be seen the very poor and the rich villages. Thus, the ADD of villages will have a big gap. It was shown that there was no significant difference between one village and another.Keywords: policy formulation, Village Fund Allocation, legislation